Blink reflex in migraine headache - TANRIDAĞ, TÜLİN (KARE PUBL, 2016)
OBJECTIVE: Activation of trigeminovascular system is thought to play an important role in migraine pathogenesis. Blink reflex (BR) test is an easy method to study the trigeminal system. Latencies recorded in BR test were evaluated to examine neurophysiological changes that occur in migraine patients. METHODS: A total of 40 patients diagnosed with migraine (9 with aura and 31 without aura) according to the International Headache Society (IHS) International Classification of Headache Disorders, 2nd edition, and 30 healthy control subjects were assessed using BR test. Supraorbital nerve was stimulated on each side, and unilateral early component (R1), and bilateral late component (R2) latencies were evaluated. RESULTS: Significantly longer latency values were recorded on both right and left sides (RR1 and LR1) as well as both ipsilateral and contralateral R2 on the left side (LR2i and LR2c) in the migraine group compared to the control group. Longer RR1 and LR1 latencies were found in patients with migraine who had an attack at the time of study (p<0.01). There was no statistically significant correlation between the location of pain and latencies in the interictal period (p>0.05). But significantly longer R1 and R2i latencies were found at the symptomatic side of patients examined during the headache attack (p=0.037 and p=0.028 respectively). There was no statistically significant correlation between the recorded latencies and gender, attack duration, attack frequency and migraine type (p>0.05). CONCLUSION: Results of BR test in the present study are thought to point to a dysfunction in brainstem and trigeminovascular connections of patients with migraine headache and support the trigeminovascular theory of migraine.
Keywords: Blink reflex; headache; migraine; TENSION-TYPE HEADACHE; BRAIN-STEM ACTIVATION; ALLODYNIA; SENSITIZATION; AFFERENTS; MENINGEAL; NEURONS; SYSTEM; NERVE; PAIN